COLLABORATIVE GOVERNANCE DALAM PELAKSANAAN KEBIJAKAN PENDIDIKAN PADA MASA PANDEMI COVID-19 DI WILAYAH PERBATASAN KALIMANTAN BARAT - Rupita Rupita; Yulianti Yulianti; Zakiah Hasan Gaffar; Syarifah Ema Rahmaniah; Herlan Herlan (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2021)
Education policy during the COVID-19 pandemic prioritizes safety and health, both learners, educators and the community. This policy is based on the Joint Decree (SKB) of four ministers that is still valid to this day. The priority in implementing this policy is collaborative governance, where every layer of society actively participates from formulation to policy implementation. This research specifically discusses the implementation of education policies in the Indonesia-Malaysia border region, Entikong West Kalimantan. This research method is the exploration of primary data and secondary data. Field primary data is obtained through observation and secondary data through literature review with topic clustering; collaborative governance, education policy, and learning in times of pandemics. Based on the discussion, the concept of collaborative governance has not been fully implemented in the application of education policy in the pandemic period. This is because there is an urgent situation in the implementation of online learning. While in collaborative governance, more activities are carried out face-to-face; Such as socialization and community participation